CREATION OF DIGITAL MAPS FOR AGROPHYSICAL PROPERTIES OF IRRIGATED MEADOW-ALLUVIAL SOILS BASED ON GEOINFORMATION TECHNOLOGIES (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article presents the results of the research on the creation of various thematic maps using modern geoinformation technologies based on the research results on the agrophysical properties of irrigated meadow-alluvial soils.